2017
DOI: 10.3389/fpls.2017.01125
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of the 2A Ribosomal Skip Principle to Tobacco Mosaic Virus for Peptide Display

Abstract: Plant viruses are suitable as building blocks for nanomaterials and nanoparticles because they are easy to modify and can be expressed and purified using plants or heterologous expression systems. Plant virus nanoparticles have been utilized for epitope presentation in vaccines, for drug delivery, as nanospheres and nanowires, and for biomedical imaging applications. Fluorescent protein fusions have been instrumental for the tagging of plant virus particles. The monomeric non-oxygen-dependent fluorescent prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 55 publications
(67 reference statements)
1
43
0
Order By: Relevance
“…The N and C termini of the TMV capsid point outwards from an assembled TMV disk ( Fig. 1A) and majority of previous vaccine design efforts have used these N and C termini to display epitopes (41,(49)(50)(51)(52). Dedeo et al (53) reported a "circular permutant" of TMV where the N and C termini were re-engineered to the inner pore and a short loop was placed to close the sequence gap.…”
Section: Resultsmentioning
confidence: 99%
“…The N and C termini of the TMV capsid point outwards from an assembled TMV disk ( Fig. 1A) and majority of previous vaccine design efforts have used these N and C termini to display epitopes (41,(49)(50)(51)(52). Dedeo et al (53) reported a "circular permutant" of TMV where the N and C termini were re-engineered to the inner pore and a short loop was placed to close the sequence gap.…”
Section: Resultsmentioning
confidence: 99%
“…The PVX-based vectors we used to produce recombinant particles displaying the iLOV polypeptide are shown in Figure 1(a) . The iLOV sequence was amplified from source vector pSC1001a (Dr. S. Chapman, The James Hutton Institute, Dundee, Scotland) using the primers listed in Table 1 and was transferred to pCR2.1-TOPO as previously described [ 57 ]. An iLOV fragment was isolated from this intermediate vector using NheI and BspEI and was transferred to vector pTCXIIc [ 37 ] either as a direct fusion (replacing the mCherry and FMDV 2A genes) or as fusion via the FMDV 2A sequence (replacing only the mCherry gene).…”
Section: Methodsmentioning
confidence: 99%
“…The integrity of the resulting vectors pPVX-iLOV-CP, pPVX-iLOV-2A-CP, and pPVX-iLOV-G 4 S-CP was tested by PCR and sequencing. The vectors were propagated in Escherichia coli strain DH5 α ready for the inoculation of Nicotiana benthamiana plants as previously described [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations